A Faith‐Based Advantage?: Comparing the Academic and Fundraising Performance of Sectarian and Nonsectarian Nonprofit Schools in Milwaukee's School Voucher Program. Issue 1 (6th July 2015) - Ford, Michael R.
Abstract : This study explored whether religiously affiliated nonprofit schools participating in Milwaukee's long‐standing school voucher program engage in more fundraising and perform better on academic indicators than nonsectarian nonprofit schools. The analysis of three years of organizational‐level voucher school data reveals that a higher percentage of religious affiliated schools engage in fundraising, and that religious schools affiliated with umbrella organizations have higher test score indicators than nonsectarian schools. The author concludes that the religious advantage is likely in part a result of the broader access to networks and resources available to religious schools associated with umbrella organizations like a Catholic archdiocese or Lutheran synod. The results are relevant to policymakers who are considering implementing a reinvented government approach to the provision of public goods, as well as leaders of nonprofit corporations who seek to maximize performance.